Metodologi Takhrīj Berbasis Rijāl: Menggabungkan Jarḥ wa al-Taʻdīl dan Evidence-Based Approach - Juwita, Frasiska Sari; Munthe , Khoirotun Nisah Br; Irhamsyah, Muhammad; Rifa’i, M. Mashduqi; Siregar, Idris (Yayasan Albahriah Jamiah Indonesia, 2025)
The study of takhrīj hadith has so far been dominated by a normative approach that positions the assessment of rijāl primarily as a reproduction of classical authority, so that the process of verifying narrator and sanad data often lacks a systematic, transparent, and methodologically traceable evaluation mechanism. This condition has implications for the limited consistency and replicability of hadith assessment in the context of contemporary hadith studies that demand higher scientific accountability. This study aims to reconstruct the methodology of takhrīj based on rijāl through the integration of the principles of jarḥ wa al-Taʻdīl with an evidence-based approach, so that the assessment of narrators and sanad is not only based on normative authority, but also on structured data management and verification. The study uses a qualitative-analytical approach with a critical analysis of rijāl literature, works of jarḥ wa al-Taʻdīl, and the scientific evidence framework that has developed in the modern research tradition. The results of this study indicate the formation of a takhrīj methodological framework that places rijāl data as the primary basis of analysis through the stages of source inventory, cross-verification of narrator information, assessment of the evidential weight of jarḥ and taʻdīl, and consistent synthesis of findings in the evaluation of sanad. This framework allows for a more structured, transparent, and consistent hadith assessment process, while minimizing subjectivity and fragmentation of assessment. The implications of this research lie in strengthening the validity and reliability of hadith assessment, as well as its contribution to developing a takhrīj methodology that is adaptive to the demands of contemporary hadith studies without abandoning the foundations of classical scholarship.